Intravitreal Tissue Plasminogen Activator Injection for Treatment-Resistant Diabetic Macular Edema of the Vitrectomized Eye - Ren Aoki (Karger Publishers, 2021)
Diabetic macular edema (DME) is the main cause of visual loss in patients with diabetic retinopathy. DME has been treated using intravitreal anti-vascular endothelial growth factor (VEGF) drugs, steroids, laser photocoagulation, vitreoretinal surgery, and their combinations. These modalities are generally effective in preserving vision, but they sometimes produce only limited responses in patients with persistent or refractory DME. The levels of various inflammatory factors, including cytokines, chemokines, and extracellular matrices, as well as VEGF in the vitreous fluid, are increased in patients with DME. Excessive fibrinogen/fibrin levels in the vitreous fluid or fibrin deposition in the retina also contribute to DME pathogenesis. Tissue plasminogen activator (t-PA) promotes the degradation of fibrinogen or fibrin. Intravitreal t-PA injection is a commonly used treatment for subretinal hemorrhage secondary to age-related macular degeneration. Intravitreal t-PA injections have previously been used to restore vision by inducing posterior vitreous detachment in patients with DME. Herein, we describe the visual outcomes of intravitreal t-PA injection in a 78-year-old woman with treatment-resistant DME in her vitrectomized eye after several previous treatments. Before the injection, her best-corrected visual acuity (BCVA) was 0.7 logMAR and central foveal retinal thickness (CRT) was 735 μm. At 1 month after the injection, her BCVA was 0.8 logMAR and CRT was 558 μm, and 3 months later, her BCVA was 0.8 logMAR and CRT was 207 μm. Her BCVA was sustained, and CRT showed gradual improvements. These findings suggested the effectiveness of intravitreal t-PA injections for DME in the vitrectomized eye.